25.0k views
5 votes
Please answer the question:

Please answer the question:-example-1
User Dwmcc
by
5.1k points

2 Answers

5 votes

Answer:

- 6

Explanation:

Given

(x - 3)² = (x - 3)(x - 3)

Each term in the second factor is multiplied by each term in the first factor, that is

x(x - 3) - 3(x - 3) ← distribute both parenthesis

= x² - 3x - 3x + 9 ← collect like terms

= x² - 6x + 9

The coefficient of the x- term is - 6

User Ericjbasti
by
5.0k points
5 votes

Answer: B) -6

Using the box method or FOIL rule, you should find that
(x-3)^2 = x^2-6x+9

An alternative is to use the perfect square formula
(a-b)^2 = a^2 - 2ab + b^2 where in this case a = x and b = 3.

User Amereservant
by
5.8k points